(untitled) (CIPEEX, 2025)
Introduction: Cervical cancer represents a serious public health issue in Brazil, with an estimated 16,710 new cases in 2023 (INCA). The Pap smear test is an essential method for cervical cancer screening, enabling early identification of cellular abnormalities. The effectiveness of clinical management strategies adopted in response to these abnormal results is crucial to prevent the progression of precursor lesions, as studies have shown that 15–30% of cases with atypical squamous cells of undetermined significance (ASC-US) may progress to high-grade lesions without proper follow-up. This study addresses the main evidence-based clinical approaches and their effectiveness in practice. Objective: To systematically analyze the recommended clinical management strategies for different abnormal Pap smear results, according to the guidelines established by INCA (2023) and the World Health Organization (2021), and to evaluate their effectiveness in preventing cervical cancer. Methods: A narrative review of scientific literature and both national and international guidelines was conducted, focusing on the Bethesda classification system and recommended follow-up protocols. Results: Low-grade results such as LSIL and ASC-US are generally managed with repeat cytology in 6 to 12 months or HPV testing, due to the high rate of spontaneous regression. High-grade results like HSIL require immediate referral for colposcopy and biopsy, with treatment (e.g., conization) initiated upon confirmation. Studies indicate that adherence to these evidence-based protocols can reduce the incidence of invasive cervical cancer by up to 70%. Conclusion: Evidence-based strategies for managing abnormal Pap smear results are highly effective in preventing cervical cancer. Proper follow-up and coordination between primary care and specialized services are essential to ensure the success of these interventions. However, challenges such as poor adherence to follow-up—especially in the North and Northeast regions of Brazil—and unequal access to colposcopy services remain significant barriers.